Guitar practice and bimanual coordination: an interdisciplinary perspective for the guitar from a pianistic technical resource (Orfeu, 2026)
In this article, we present a proposal for the application of a resource of pianistic action in guitar technique. It is an exploratory approach, which puts into perspective theoretical contributions of the neurophysiology of movement, motor learning and instrumental technique. Methodologically, it is an exploratory approach, which puts into perspective theoretical contributions of the neurophysiology of movement, motor learning and instrumental technique. From research focused on the intersection between guitar technique and coordination of bimanual skills, we realized that the general focus of the literature was more focused on digital actions than on the relative movement between the hands. We also discuss how the understanding of instrumental action from general bimanual movements can represent an important conceptual contribution to research related to bimanual coordination on the guitar. In this sense, based on the understanding of general movements as discrete actions, representatives of the motor support to smaller digital movements, it was possible to demonstrate that at least symmetrical movement (MS) can be contextualized in the guitar technique.